2011
DOI: 10.1007/s10534-011-9499-1
|View full text |Cite
|
Sign up to set email alerts
|

The unique role of siderophore in marine-derived Aureobasidium pullulans HN6.2

Abstract: The L -ornithine-N (5)-monooxygenase structural gene (SidA gene, accession number: FJ769160) was isolated from both the genomic DNA and cDNA of the marine yeast Aureobasidium pullulans HN6.2 by inverse PCR and RT-PCR. An open reading frame of 1,461 bp encoding a 486 amino acid protein (isoelectric point: 7.79) with calculated molecular weight of 55.4 kDa was characterized. The promoter of the gene (intronless) was located from -1 to -824 and had three HGATAR boxes which were putative binding motifs for the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 25 publications
0
37
0
Order By: Relevance
“…Another siderophore presenting antimicrobial properties is fusigen, produced by the yeast Aureobasidium pullulans (32,33). Wang et al (33) presented the siderophore screening of 300 yeast species confirming the production of fusigen by the previously mentioned A. pullulans.…”
Section: Pharmacological and Medical Applicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Another siderophore presenting antimicrobial properties is fusigen, produced by the yeast Aureobasidium pullulans (32,33). Wang et al (33) presented the siderophore screening of 300 yeast species confirming the production of fusigen by the previously mentioned A. pullulans.…”
Section: Pharmacological and Medical Applicationsmentioning
confidence: 96%
“…The antimicrobial activity of fusigen were confirmed in the marine pathogens Vibrio anguillarum and Vibrio parahaemolyticus. In a following report, investigators disrupted the sidA gene encoding for the siderophore and the yeast did not show antimicrobial activity against the previously mentioned marine pathogens (32). Recent genome sequencing studies showed that A. pullulans contains certain clusters of non-ribosomal peptide synthetases (NRPS) (41), which are enzymes involved in siderophore biosynthetic pathways (8,72).…”
Section: Pharmacological and Medical Applicationsmentioning
confidence: 99%
“…An extracellular protease producing Aureobasidium pullulans HN6.2 was isolated from the sediment of the sea saltern in Qingdao, China [Chi et al, 2011b] [Wang et al, 2014b]. KM, which was a high exoinulinase producer was grown in the inulinase production medium [Zhou et al, 2014].…”
Section: Strains and Cultivation Mediamentioning
confidence: 99%
“…A plasmid pCAM-BIA1381 carrying a bacterial hygromycin B phosphotransferase gene (HPT) was kindly offered by Dr. Lining Zhang in Canada [Chi et al, 2011b].…”
Section: Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation